New Method of Production and Characterization of Haemozoin and B-Haemozoin from Meccus longipennis - GONZÁLEZ-LINARES, Liliana (Iran J Parasitol, 2019)
BACKGROUND: Understanding the significance of hemozoin (Hz) in the process through which Plasmodium is released from the heme group in the food vacuole during hemoglobin degradation, will allow the development of more effective drugs against malaria. Therefore, the development of methodologies to obtain Hz synthetically will facilitate an in vitro evaluation of new anti-malarial drugs. METHODS: We present a methodology with good results to obtain Hz from fecal material of blood-sucking insects Meccus longipennis. The preparation of biological cultures of the parasite (Plasmodium) transmitter of the disease is not necessary. RESULTS: The hemozoin molecule and its dimer were obtained using the method described and it was possible to validate a comparison with the positive and negative controls using different analytical techniques. CONCLUSION: The proposed method allows obtaining hemozoin and its dimer demonstrating equivalence with positive controls that demonstrate that the present procedure may be an alternative for the evaluation of antimalarial drugs.